Temperature‐Dependent CO2 Electroreduction over Fe‐N‐C and Ni‐N‐C Single‐Atom Catalysts. Issue 51 (8th November 2021) - Lin, Long; Li, Haobo; Wang, Yi; Li, Hefei; Wei, Pengfei; Nan, Bing; Si, Rui; Wang, Guoxiong; Bao, Xinhe
Abstract: Reaction temperature is an important parameter to tune the selectivity and activity of electrochemical CO2 reduction reaction (CO2 RR) due to different thermodynamics of CO2 RR and competitive hydrogen evolution reaction (HER). In this work, temperature‐dependent CO2 RR over Fe‐N‐C and Ni‐N‐C single‐atom catalysts are investigated from 303 to 343 K. Increasing the reaction temperature improves and decreases CO Faradaic efficiency over Fe‐N‐C and Ni‐N‐C catalysts at high overpotentials, respectively. CO current density over Fe‐N‐C catalyst increases with temperature, then gets into a plateau at 323 K, finally reaches the maximum value of 185.8 mA cm −2 at 343 K. While CO current density over Ni‐N‐C catalyst achieves the maximum value of 252.5 mA cm −2 at 323 K, and then drops significantly to 202.9 mA cm −2 at 343 K. Temperature programmed desorption results and density functional theory calculations reveal that the difference of temperature‐dependent variation on CO Faradaic efficiency and current density between Fe‐N‐C and Ni‐N‐C catalysts results from the varied adsorption strength of key reaction intermediates during CO2 RR. Abstract : Fe‐N‐C and Ni‐N‐C catalysts show different temperature‐dependent CO2 RR performance due to their different adsorption behaviour of key reaction intermediates.